Application of autologous fibroblasts in correcting involution-dystrophic skin changes - Tsepkolenko, Volodymyr; Tsepkolenko, Hanna (Aesthetic Medicine, 2023)
This article delves into the clinical, instrumental and immunological studies of facial involutional-dystrophic skin changes in female patients of different ages with the development of a clinical method within their treatment called neofibrolifting. This method utilizes the transplant of autologous fibroblasts into the pretreated patient with platelet-rich plasma skin. Planning the proper treatment plan was based on the data of the transplanted cells properties as well as the instrumental and immunological studies of the patients’ dermis. Aging is a complex biological process of metabolic and structural-functional changes in the body, covering all human organs and tissues. Skin aging is part of the irreversible biological processes occurring in the body and is caused by genetic disorders, telomere shortening, resistance of cellular structures to oxidative damage, as well as aggressive environmental influences1. The properties and functions of the skin and its appendages deteriorate with age, the skin loses moisture, the ability to regenerate, becomes thinner, and the processes of keratinization, pigmentation, blood circulation, collagen synthesis, etc.are disrupted2,3. There is an accumulation of data on the significant involvement of the involution of the immune system in overall skin aging, which is generally defined as the process of immunosenescence4,5. This manifests through mechanisms known as age-related disorders in the compartments of hematopoietic stem and multipotent stromal cells with the inhibition of hematopoiesis and disorders in the regulation of immunoneuroendocrine6,7. There is a shift of cellular cooperative mechanisms towards the formation of chronic inflammations with the increased production of pro-inflammatory cytokines by adaptive and innate immune cells, which cause the appearance of a large number of senescent and terminally differentiated cells that are not able to perform the necessary functions8. Immunosenescent atrophic and dystrophic phenomena in the skin are manifested by a pronounced decrease in the number of dermal fibroblasts with the inhibition of their functional activity, which also negatively affects the condition of keratinocytes. As a result, the normal process of renewal of dermal fibroblasts and keratinocytes, the formation of the intercellular matrix, is disrupted, which primarily causes the appearance of noticeable involutional signs9-11.